“Write here, sanctuary” Creative writing for refugees and people seeking asylum - Stickley, Theodore; Hui, Ada M.L.; Stubley, Michelle; Baker, Francesca; Watson, Michael Craig (Taylor and Francis, 2018)
Background There are few research studies reporting findings from creative writing groups amongst refugees and people seeking asylum. This study evaluates the educational, wellbeing, social and satisfaction outcomes of writing groups across three cities in the UK. Methods This study employs a mixed-method design comprising: a thematic analysis of writers’ (facilitators) diaries, demographic and satisfaction survey and 14 qualitative interviews. Results The project delivered a creative writing programme for refugees and people seeking asylum in three UK cities. This evaluation has determined that it provided both educational and wellbeing outcomes for 144 attendees. Participants asserted that they had improved their English language and wellbeing. Satisfaction was extremely high across the cities. Participants reported increased confidence and an increased sense of hope. Conclusions Professionally-led creative writing groups may be effective in enabling people to help come to terms with past experiences and find ways of coping for the future.